2021
DOI: 10.1002/ece3.8252
|View full text |Cite
|
Sign up to set email alerts
|

A comparative analysis of spider prey spectra analyzed through the next‐generation sequencing of individual and mixed DNA samples

Abstract: As one of the most abundant predators of insects in terrestrial ecosystems, spiders have long received much attention from agricultural scientists and ecologists. Do spiders have a certain controlling effect on the main insect pests of concern in farmland ecosystems? Answering this question requires us to fully understand the prey spectrum of spiders. Next-generation sequencing (NGS) has been successfully employed to analyze spider prey spectra. However, the high sequencing costs make it difficult to analyze t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 62 publications
3
4
0
Order By: Relevance
“…However, the life stage of prey cannot be identified by the present method because the primers were not specific to any life stage (Yang, Liu, Yuan, Zhang, Peng, et al, 2017). Similar to the results of Yang et al (2021), a few spider species ( Neoleptoneta sp., Pardosa sp., and Theridion sp. ; Table ) were included in the prey spectrum of C. blandum , thus indicating intraguild predation (Michalko et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…However, the life stage of prey cannot be identified by the present method because the primers were not specific to any life stage (Yang, Liu, Yuan, Zhang, Peng, et al, 2017). Similar to the results of Yang et al (2021), a few spider species ( Neoleptoneta sp., Pardosa sp., and Theridion sp. ; Table ) were included in the prey spectrum of C. blandum , thus indicating intraguild predation (Michalko et al, 2021).…”
Section: Discussionsupporting
confidence: 89%
“…Universal primer pairs (mlCOIintF/Fol‐degen‐rev) can amplify the COI gene in the prey remains within the spider's gut as well as in the spider itself. Similar to the results of Piñol et al (2014) and Yang et al (2021), the sequence annotation showed that most of the sequences belonged to the predator itself, which accounted for 90.9% of the total sequences. In addition, nonprey sequences (including fungi, Chordata, aquatic taxa (Cnidaria, Rotifera, Bacillariophyta, Phaeophyta, Rhodophyta, and some aquatic arthropods) and soil‐dwelling taxa (Annelida)) were found in the sequencing results, which accounted for 1.6% of the total sequences.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations